Sintese, caracterização e eletroatividade de sams formadas com compostos catiônicos de tetraaminas de rutênio - Pinheiro, Solange de Oliveira (2006)
Trans-[Ru(CNpy)(NH3)4(L)]2+ type complexes, where CNpy (4- Cyanopyridine), L= 1,4-dt (1,4-dithiane), pyS (4-mercaptopyridine), and Tio (thionicotinamide), were synthesized and characterized by HPLC, microanalysis, eletrochemistry and vibrational and eletronic spectroscopies. The eletrochemical and eletronic absorption results are indicative of a π back-bonding interaction, L(nπ*) ← RuII(dπ) for which L is the pyS, CNpy and Tio ligands. The half-wave formal potentials (E1/2) observed for the trans-[Ru(CNpy)(NH3)4(pyS)]2+, trans- [Ru(CNpy)(NH3)4(1,4-dt)]2+ and trans-[Ru(CNpy)(NH3)4(Tio)]2+ complexes: 1.00, 0.67 and 1.03 V vs NHE, respectively, are indicative of the stabilization of the metal in the reduced state comparatively to the start complex, trans-[Ru(CNpy)(NH3)4(OH2)]2+ (E1/2 = 0.35 V vs NHE). This result indicates, also, the strong π withdraw capability of the CNpy ligand. The shift observed for the νC≡N mode from 2239 cm-1 in the vibrational spectra of the CNpy free ligand to ∼2200 cm-1 upon coordination suggests that the coordination occurs through the nitrile fragment. For the pyS and Tio ligands, the observation of the signals assigned to the νC=S and νSH modes, respectively, in the vibrational spectra os the complexes indicates that the coordination occurs through the nitrogen atom os the pyridine ring. The SERS ex situ spectra of the gold surfaces modified with the isolated complexes allow the classification of these species as binfunctional molecules in which the sulfur atom of the pyS, 1,4-dt and Tio ligands is the adsorption site and the nitrogen atom of the CNpy pyridine ring is the functional terminal group. Also, the SERS results point for a trans conformation for the trans- [Ru(CNpy)(NH3)4(pyS)]2+ complex and for a gauche configuration for the trans- [Ru(CNpy)(NH3)4(1,4-dt)]2+ and trans-[Ru(CNpy)(NH3)4(Tio)]2+ complexes on gold. The intensity dependence of some signals in the SERS spectra with the applie potential reflects the π back-bonding effect on surface since this behavior is observed to be strongly related to the E1/2 values of the complexes. The reductive desorption potentials of the SAMs formed with the isolated compounds reflects the π withdraw capability of the CNpy ligand. This effect is much more intense for the trans-[Ru(CNpy)(NH3)4(1,4-dt)]2+ complex since the π back-bonding interaction of the 1,4-dt ligand is lower than the CNpy, pyS and Tio ligands. The heterogeneous electron transfer reaction of the cytochrome c metalloprotein was satisfactorily assessed with the SAMs formed by the isolated complexes (E1/2 = 0.05 V vs Ag⏐AgCl⏐Cl-). The Best voltammetric response was observed with the SAM of the trans- [Ru(CNpy)(NH3)4(pyS)]2+ complex due to the trans conformation on surface.